2008
DOI: 10.1007/s00122-008-0830-3
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel cytoplasmic male-sterility and its restorer lines in radish (Raphanus sativus L.)

Abstract: A male-sterile (MS) radish (Raphanus sativus L.) was found in an accession collected from Uzbekistan. Unlike Ogura MS radishes in which no pollen grain is typically visible during anthesis, a small number of pollen grains stuck together in the dehiscing anthers was observed in the newly identified MS radish. Fluorescein diacetate tests and scanning electron micrographs showed that pollen grains in the new MS radish were severely deformed and non-viable. Cytological examination of pollen development stages show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 49 publications
4
45
0
1
Order By: Relevance
“…The mitochondrial gene, orf138, responsible for male-sterility induction (Bonhomme et al 1991;Grelon et al 1994), along with the fertility restorer gene, Rfo, were cloned (Brown et al 2003;Desloire et al 2003;Koizuka et al 2003). Male-sterility conferred by a different cytotype, DCGMS, was recently discovered (Lee et al 2008). At first, this was assumed to be complete CMS line without any fertility restorers since most breeding lines actually maintained CMS.…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial gene, orf138, responsible for male-sterility induction (Bonhomme et al 1991;Grelon et al 1994), along with the fertility restorer gene, Rfo, were cloned (Brown et al 2003;Desloire et al 2003;Koizuka et al 2003). Male-sterility conferred by a different cytotype, DCGMS, was recently discovered (Lee et al 2008). At first, this was assumed to be complete CMS line without any fertility restorers since most breeding lines actually maintained CMS.…”
Section: Introductionmentioning
confidence: 99%
“…The pollen number might be related with the development of meiosis of microspore mother cell, or the daparture of pollen grains from tapetum and the realeasement from anther, and the pollen viability might be related with normal development of pollen grains after meiosis of microspore mother cell. Lee et al (2008) reported that no pollen grain is typically visible during anthesis in a male sterile radish, but a small number of pollen grains could be observed stuck together in the dehiscing anthers in another male sterile radish. Gothandam et al (2007) showed that pollen viability and grain production decreased significantly when treated at a low temperature in a rice MS line, and the male sterility is due to functional loss of the tapetum which is the most sensitive to low-temperature stress.…”
Section: Discussionmentioning
confidence: 99%
“…The F 1 hybrid was produced in a previous study (Lee et al 2008). F 2 seeds were germinated in a greenhouse in 128-cell plug trays measuring 54 9 28 9 8 cm 3 .…”
Section: Plant Materialsmentioning
confidence: 99%
“…In the past decade, a new CMS, designated Dongbu cytoplasmic and genic male-sterility (DCGMS), was discovered in radish germplasm introduced from Western Europe (Lee et al 2008). Cytological examination of pollen development of DCGMS plants showed that microspore abortion occurred at later stages than in Ogura CMS plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation